Association of DNA Methylation-Based Biological Age With Health Risk Factors and Overall and Cause-Specific Mortality. Issue 3 (17th August 2017) - Dugué, Pierre-Antoine; Bassett, Julie K; Joo, JiHoon E; Baglietto, Laura; Jung, Chol-Hee; Wong, Ee Ming; Fiorito, Giovanni; Schmidt, Daniel; Makalic, Enes; Li, Shuai; Moreno-Betancur, Margarita; Buchanan, Daniel D; et al.
Abstract: Measures of biological age based on blood DNA methylation, referred to as age acceleration (AA), have been developed. We examined whether AA was associated with health risk factors and overall and cause-specific mortality. At baseline (1990–1994), blood samples were drawn from 2, 818 participants in the Melbourne Collaborative Cohort Study (Melbourne, Victoria, Australia). DNA methylation was determined using the Infinium HumanMethylation450 BeadChip array (Illumina Inc., San Diego, California). Mixed-effects models were used to examine the association of AA with health risk factors. Cox models were used to assess the association of AA with mortality. A total of 831 deaths were observed during a median 10.7 years of follow-up. Associations of AA were observed with male sex, Greek nationality (country of birth), smoking, obesity, diabetes, lower education, and meat intake. AA measures were associated with increased mortality, and this was only partly accounted for by known determinants of health (hazard ratios were attenuated by 20%–40%). Weak evidence of heterogeneity in the association was observed by sex ( P = 0.06) and cause of death ( P = 0.07) but not by other factors. DNA-methylation-based AA measures are associated with several major health risk factors, but these do not fully explain the association between AA and mortality. Future research should investigate what genetic and environmental factors determine AA.